Comparing concentration‐based (AOT40) and stomatal uptake (PODY) metrics for ozone risk assessment to European forests. (6th January 2016) - Anav, Alessandro; De Marco, Alessandra; Proietti, Chiara; Alessandri, Andrea; Dell'Aquila, Alessandro; Cionni, Irene; Friedlingstein, Pierre; Khvorostyanov, Dmitry; Menut, Laurent; Paoletti, Elena; Sicard, Pierre; Sitch, Stephen; et al.
Abstract: Tropospheric ozone (O3 ) produces harmful effects to forests and crops, leading to a reduction of land carbon assimilation that, consequently, influences the land sink and the crop yield production. To assess the potential negative O3 impacts to vegetation, the European Union uses the Accumulated Ozone over Threshold of 40 ppb (AOT40). This index has been chosen for its simplicity and flexibility in handling different ecosystems as well as for its linear relationships with yield or biomass loss. However, AOT40 does not give any information on the physiological O3 uptake into the leaves since it does not include any environmental constraints to O3 uptake through stomata. Therefore, an index based on stomatal O3 uptake (i.e. PODY), which describes the amount of O3 entering into the leaves, would be more appropriate. Specifically, the PODY metric considers the effects of multiple climatic factors, vegetation characteristics and local and phenological inputs rather than the only atmospheric O3 concentration. For this reason, the use of PODY in the O3 risk assessment for vegetation is becoming recommended. We compare different potential O3 risk assessments based on two methodologies (i.e. AOT40 and stomatal O3 uptake) using a framework of mesoscale models that produces hourly meteorological and O3 data at high spatial resolution (12 km) over Europe for the time period 2000–2005. Results indicate a remarkable spatial and temporal inconsistency between the two indices, suggesting that a new definition of European legislative standard is needed in the near future. Besides, our risk assessment based on AOT40 shows a good consistency compared to both in‐situ data and other model‐based datasets. Conversely, risk assessment based on stomatal O3 uptake shows different spatial patterns compared to other model‐based datasets. This strong inconsistency can be likely related to a different vegetation cover and its associated parameterizations.